Barriers to employment of Australian cancer survivors living with geographic or socio‐economic disadvantage: A qualitative study - Emma Kemp; Vikki Knott; Paul Ward; Suzana Freegard; Ian Olver; Julia Fallon‐Ferguson; Jon Emery; Chris Christensen; Monique Bareham; Bogda Koczwara (Wiley, 2021)
Abstract Background Opportunities for cancer survivors' employment can both reflect and perpetuate health inequities, as employment is an important social determinant of health. Socio‐economic and geographic disadvantage is associated with greater difficulty finding work, but little is known about work needs of Australian cancer survivors living with disadvantage. Objective This study examined survivor and health‐care professional (HCP) perspectives on barriers experienced by Australian cancer survivors experiencing disadvantage when attempting to remain at or return to work. Method Focus groups and individual interviews were held with cancer survivors (N = 15) and oncology and primary HCPs (N = 41), focusing on communities at risk of disadvantage. Participants were asked about employment barriers and facilitators in general and in the context of disadvantage. Themes were identified using framework analysis. Results Geographic and socio‐economic disadvantage resulted in specific individual‐ and system‐level barriers. These related to distance from treatment and support services and limited availability and suitability of work for survivors living with geographic disadvantage, and limited availability, security, and flexibility of work and previous unemployment for survivors living with socio‐economic disadvantage. Identified needs included system‐level changes such as public and workplace‐level education, legislative and policy changes, and better access to resources. Conclusions Cancer survivors living with disadvantage experience limited access to flexible employment opportunities and resources, further perpetuating their disadvantage. Promotion of health equity for cancer survivors living with disadvantage requires systemic changes to support attempts to remain at/return to work. Patient or public contribution This study included cancer survivors and HCPs as investigators, authors and participants.